Determinants of Sustainable Development in the Non-Cyclical Consumer Sector: Case in Indonesia - Wijayanti, Rista Putri; Sari, Shinta Permata (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The concept of Sustainable development is interpreted as development without sacrificing environmental interests or always paying attention to environmental aspects. In this concept, every improvement must pay attention to environmental rights intended to create sustainable development without reducing and sacrificing the ability of future generations to achieve and enjoy their welfare. This study aims to examine the effect of green accounting, material flow cost accounting, environmental performance, and environmental costs on sustainable development with a case study of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange. The study uses a quantitative approach using data from annual reports and financial statements of companies in the sector for 2021 to 2023, including numerical information. The sample is selected using purposive sampling techniques to ensure adherence to established criteria. Data analysis is performed using multiple regression analysis. The study results show that green accounting, material flow cost accounting, and environmental performance have an impact on sustainable development, but environmental costs do not have a significant effect.